Accessibility of Young Farmers Towards the Government's Paddy Agricultural Aid Program in The MADA Administration Area - Mohamed Salleh, Ahmad Naim; Samsurijan, Mohamad Shaharudin; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2024)
The role of young farmers in the paddy agriculture sector is vital for ensuring the sustainability and progression of agricultural activities. Therefore, it is crucial that young farmers receive attention from various parties to gain access to government aid for paddy agriculture. This study aims to address three objectives: identifying the challenges young farmers face in accessing government programs and aid for paddy agriculture, understanding the importance of accessibility to these programs and aid for young farmers, and exploring strategies to enhance accessibility. For this study, a qualitative approach was adopted, and 15 respondents were interviewed individually. The findings reveal that the main issue and challenge faced by young farmers is their lack of preparedness to access government aid for paddy agriculture. The study also explores the importance of government aid for young farmers through the insights gathered during the interviews. Five key benefits of government paddy agriculture aid for young farmers were identified: reducing operational costs, increasing revenue, lightening the workload, improving fertilizing and harvesting techniques, and increasing paddy farming yields. Finally, the study proposes practices to enhance accessibility for young farmers, which include empowering their skills and abilities, strengthening public institutions, and improving infrastructure facilities. These findings can serve as a benchmark for future endeavors and guide interested parties in their efforts to support young farmers.